Ocular tuberculosis: Clinicopathologic assortment and diagnostic challenges - Priyatam Khadka; Ranju Kharel (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2019)
Ocular tuberculosis is an exigent clinical entity-lacking a distinct clinical presentation and attributing the diagnostic conundrum. Nevertheless, the early-precise diagnosis with implicated anti-tubercular therapy may be sight-saving; diagnostic delays often encountered due to protean clinical presentations, the impracticability of obtaining tissue (in most case), limitation on sample volume extraction, and of wanting a sensitive diagnostic test. This article revises the current scenario of ocular tuberculosis, its clinicopathologic arrays, and diagnostic challenges for clinical management; Furthermore, advocates for compiling all such positive findings of corroborative tests in a precise diagnosis.